Growth and Yield of Intercropping between Carica (Carica pubescens) and Sweet Potato (Ipomoea batatas L.) and Leeks (Allium fistulosum L.) - Adi Rastono; Sugiyarto Sugiyarto; Marsusi Marsusi (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Carica pubescens needs a climate and edapic environment similar to that of its native Dieng plains in order to thrive. Due to these circumstances, measures must be taken to facilitate its diffusion. Another option is transplanting to regions with nearly identical edaphic and climatic characteristics. The growth of C. pubescens planted in monoculture and intercropping, as well as the degree of crop competition in intercropping and the effectiveness of the land used, the slopes of Mount Lawu are advised for transplant. The study's planting treatments were as follows: (1) C. pubescens monoculture; (2) Sweet Potato Monoculture; (3) C. pubescens and Sweet Potato Combination; (4) Leek Monoculture; and (5) C. pubescens and Scallions Combination. The study was set up in a randomized block design (RBD) with five replications. The ANOVA analysis of the growth characteristics, which comprised planting height, leaf area, and the number of leaves, was then proceeded using Duncan's test at the 5% level. Utilize the competition ratio (CR) formula to determine plant competition and the land equivalent ratio (LER) formula to determine productivity. The number of leaves parameter in the C. pubescens and sweet potato combination indicated a significant difference in the results. When grown alongside sweet potatoes, C. pubescens tends to be less competitive, with plant height values of 0.86: 1.27, 0.83: 1.72 for leaves, and 0.94: 1.10 for leaf area. The intercropping system is more lucrative with a value of plant height: 1.84, number of leaves: 1.89, and leaf area: 1.99 compared to plant height: 2, number of leaves: 2, and leaf area: 2, 25.